Fallen [videorecording (DVD)] - Hoblit, Gregory; Washington, Denzel, 1954-; Goodman, John, 1952-; Sutherland, Donald, 1935-; Gandolfini, James (Warner Home Video, 1998)
Detective John Hobbes is searching for a criminal he's already met, already caught and already killed.